Implementation of Guided Inquiry Learning Method in Creating Color Composition in Middle School Students - Hasniah S; Sukarman, Sukarman; Husain, Muh. Saleh (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The background of this research stems from the need for a more active and student-centered learning approach to increase engagement, creativity, and understanding of color concepts, especially primary, secondary, and tertiary colors. This study aims to evaluate the application of the guided inquiry learning method in creating color compositions in the Arts and Culture (Fine Arts) subject in junior high schools in Takalar Regency. The methodology used in this study is an evaluative method with a qualitative approach. Data were collected through observation, interviews, and document analysis. The results of the study indicate that the application of the guided inquiry method significantly improves students' understanding of the concept of color and their ability to create color compositions independently and creatively. In addition, this method also encourages the students' active involvement, teamwork, and critical thinking skills. Although it requires more time and effective classroom management, this method has proven relevant and effective for application in fine arts learning at the junior high school level.